A silent trio: Giant descending aortic aneurysm combined with coarctation and persistent left brachiocephalic truncus. Issue 8 (25th August 2021) - Basho, Maksim; Nunci, Deniona; Vyshka, Gentian; Prifti, Edvin
Abstract: We report a case of an undiagnosed descending aortic aneurysm, combined with coarctation and persistent left brachiocephalic truncus in a 59‐year‐old male. It highlights the necessity for aortic imaging, when facing a poorly controlled hypertension. Abstract : We report a case of an undiagnosed descending aortic aneurysm, combined with coarctation and persistent left brachiocephalic truncus in a 59‐year‐old male. It highlights the necessity for aortic imaging, when facing a poorly controlled hypertension.